The viscount's Christmas bride - Scott, Bronwyn, 1967- (Harlequin historicals., 2024)
Pretend proposal under the mistletoe... Real wedding by Christmas? Newly minted viscount Julien has his desire for a peaceful Christmas thwarted by some unwelcome houseguests... Years ago, Lady Aurelia refused Julien's marriage offer. Now she's on his doorstep, and this time her recently impoverished father is encouraging a betrothal! But proud Julien won't risk his heart again... Being forced to reject Julien left Aurelia stricken, and now she guards her feelings closely. Tired of being a pawn, she proposes a pretend courtship to prevent further meddling from her father. But will the terms of their festive union change when they're reminded of their passionate connection?